(untitled) (Journal of Bangladesh Academy of Sciences, 2013)
Three steroids, namely 24-ethyl-5?-cholestan-3-one (1), 5?-stigmast-22-en-3-one (2), stigmast-5, 22-dien-3-one (3) have been isolated from N. stellata. The phytochemical and antimicrobial as well as cytotoxic activities of Nymphaea stellata were investigated in this study. Crude extracts of N. stellata and various column fractions exhibited poor antimicrobial activity against a wide range of Gram-positive and Gram-negative bacteria and fungi. The crude extract and the fractions showed significant cytotoxic effect when subjected to brine shrimp lethality bioassay. DOI: http://dx.doi.org/10.3329/jbas.v37i1.15687 Journal of Bangladesh Academy of Sciences, Vol. 37, No. 1, 109-113, 2013